2016
DOI: 10.1016/j.cirp.2016.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Natural fibre selection for composite eco-design

Abstract: Natural fibre composites (NFC) are gaining interest in manufacturing because they address some of the environmental problems of traditional composites: use of non-renewable resources, and large impacts related to their production and disposal. Since natural fibres are not yet optimized for composite production, it is crucial to identify the most appropriate applications, and determine the optimal fibre/matrix ratio. A methodology is proposed for early-stage decisions support on selection of bio-composite mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Micromechanics of materials can be measured by using micromechanical properties such as mechanical and physical properties. An integrated method with a micromechanical model is used to perform the life cycle assessment [22]. In addition, micromechanical model is used to classify heterogeneous materials like composite [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Micromechanics of materials can be measured by using micromechanical properties such as mechanical and physical properties. An integrated method with a micromechanical model is used to perform the life cycle assessment [22]. In addition, micromechanical model is used to classify heterogeneous materials like composite [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the production processes used in making these synthetic fibers are energy intensive. Corona et al (2016) analyzed the potential of using plant based natural fibers to replace synthetic fibers in composites. Using life cycle assessment (LCA), they concluded that replacement of glass fibers with flax fibers show a general reduction of the environmental impact regardless of the type of application.…”
Section: Composite Materials Innovationmentioning
confidence: 99%
“…It shows that tradeoffs between environmental benefits and environmental burdens can occur when compared to fossil-based materials. Although biocomposites have been found to have lower environmental impacts when compared to materials made from fossil plastics for several important impact categories, including, human toxicity, ecotoxicity, resource depletion, and climate change (Corona et al, 2016;Deng et al, 2016;Duigou and Baley, 2014;Rosa et al, 2014), they can cause environmental impacts related to eutrophication, land use and climate change impacts due to agriculture (Kim et al, 2008;Korol et al, 2016;Papong et al, 2014). Kim et al, 2008 showed that surface modification of natural fibers using chemicals contributed to impacts from photochemical smog, acidification and eutrophication.…”
Section: Introductionmentioning
confidence: 99%